Gutsch Editions. (Berlin - New York : Gutsch Editions, 1995)
Assig, Martin ; Baechler, Donald ; Badur, Frank ; Klein, Astrid ; Donvie, Rudolf ; Buthe, Michael ; Christian, Abraham D. ; Dokoupil, Jiri Georg ; Zimmer, Bernd ; Lang, Nikolaus ; Henderikse, Jan ; Hörl, Ottmar ; Lüscher, Ingeborg ; Badur, Frank ; Klauke, Jürgen ; Kuroda, Aki, ; Merz, Albert ; Mira, Victor ; Penck, A.R. ; Quandt, Barbara ; Rheinsberg, Raffael ; Strawalde
Duits
boek